2011
DOI: 10.4103/0970-4388.85825
|View full text |Cite
|
Sign up to set email alerts
|

The most effective and essential way of improving the oral health status education

Abstract: The results of various parameters indicate that direct communication through the dentist proved to be the most effective communication approach as compared to the other two indirect communication approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 0 publications
1
23
2
3
Order By: Relevance
“…Einwag et al, in their study noted a positive effect of supervised brushing of teeth on the improvement of the state of oral hygiene in adolescents [20]. The current study, similar to other studies, shows that the direct patient-dentist communication may be one of the most effective methods for the improvement of oral hygiene and health promoting behaviours [21,22]. …”
Section: Discussionsupporting
confidence: 83%
“…Einwag et al, in their study noted a positive effect of supervised brushing of teeth on the improvement of the state of oral hygiene in adolescents [20]. The current study, similar to other studies, shows that the direct patient-dentist communication may be one of the most effective methods for the improvement of oral hygiene and health promoting behaviours [21,22]. …”
Section: Discussionsupporting
confidence: 83%
“…Study involving maximum no. of students was conducted by Chachra et al, [15] in which the authors involved 972 students in their study. In all the other studies, the final sample size of the study population was not more than 500.…”
Section: Resultsmentioning
confidence: 99%
“…Four of the studies used randomized controlled designs and provided adequate data for inclusion in the formal meta-analysis [10,12,15,18]. Three of the studies used plaque as one of their outcomes and only one used DMFT and DMFS index for assessing the oral hygiene status after conducting dental health education.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature review identified seven studies conducted in India assessing the effect of school based oral health education on oral health outcomes (Parkash et al, 2004;Grewal et al, 2009;Ajithkrishnan et al, 2010;Bhardwaj et al, 2013;Gauba et al, 2013;Gambhir et al, 2013;Chachra et al, 2011). Because school based oral health education is in the early stages of development, the majority of these studies focused on guideline development rather than effective oral health education strategies.…”
Section: Introductionmentioning
confidence: 99%